Violations of Forest Laws in the Bu Gia Map National Park, Vietnam. Issue 2 (1st February 2022) - Nguyen, Toai; Lawler, Susan; Vuong, Hoa; Huynh, Da
Abstract: Serious violations of forest laws often provoke violent conflicts between managers of protected areas and local people. Understanding who commits serious violations may enable forest managers to create relevant intervention strategies based on violators' profiles. Previous studies have not examined the profiles of violators to have a better picture of the impacts of people on natural forests within protected areas. In this study, we examined violation records within the Bu Gia Map National Park to illustrate the profiles of the violators of forest laws. We described and analyzed the profiles of violators in the Bu Gia Map National Park, and we found that indigeneity, group violations, residential locations, genders, and seasonal variations are statistically significant in explaining the serious violation committed by local people. We expect this analysis will enable park managers to have better intervention strategies to protect natural forests from human activities. Impact statement: This study will support park managers in creating relevant intervention strategies for the conservation of natural forests.